AN ENVIRONMENTAL ACCOUNTING APPROACH IN ANALYZING THE IMPACT OF THE ECOTOURISM INDUSTRY, INNOVATION, INFRASTRUCTURE INVESTMENT, AND GREEN ECONOMY ON SUSTAINABLE CITIES AND COMMUNITIES IN THE MANDALIKA SPECIAL ECONOMIC ZONE, WEST NUSA TENGGARA - Mulia Rahmah; Arisetyanto Nugroho; Darmansyah, Darmansyah (Bajang Institute, 2025)
The development of sustainable cities and communities is an integral part of the Sustainable Development Goals (SDGs), particularly SDG 11. The Mandalika Special Economic Zone (SEZ) in West Nusa Tenggara has been designated as a national strategic project that requires environmentally oriented and participatory development governance. This study aims to analyze the influence of the ecotourism industry, innovation and creativity, infrastructure investment, and green economic practices on the development of sustainable cities and communities, using the environmental accounting approach as the conceptual framework. A quantitative approach is employed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Data were collected through a survey of 210 respondents consisting of tourism actors, zone authorities, local communities, and investors. The results reveal that all independent variables—ecotourism industry, innovation, infrastructure investment, and green economy—have a positive and significant impact on sustainable cities and communities. Among these, green economic practices made the most dominant contribution. Furthermore, environmental accounting is proven to have a mediating role in strengthening the impact of these variables on regional sustainability. These findings highlight that environmental accounting functions not only as a reporting tool but also as a strategic instrument for enhancing transparency, accountability, and performance evaluation of sustainable development in the Mandalika SEZ. This study contributes theoretically to the development of environmental accounting studies and provides practical implications for managing national strategic zones through a sustainability lens.